Komunikasi Organisasi Sebagai Penguatan Kelembagaan Di Sektor Pertanian (Kasus Alih Fungsi Lahan Pertanian Di Kabupaten Sleman) - Paksi Penggalih; Hermin Wahyuni; Trisakti Haryadi; Alia Raya (UPT Penerbitan Universitas Jember, 2018)
One of the ways in which institutional strengthening among several organizations canbe done through communication. Organizational communication that work well can encourage theachievement of an organizational goal. The case of conversion of agricultural land that occurs inSleman Regency really requires the role of local government institutions so that the rate of landconversion is not higher. In carrying out its role, good communication between governmentinstitutions is needed to strengthen collaboration between institutions in an effort to control therate of conversion of agricultural land in Sleman Regency. Based on this fact, this study aims todescribe how communication organizations working in Sleman Regency government institutionsto strengthen institutions in the agricultural sector in the case of land conversion. This study usesqualitative methods for descriptive purposes. The subjects of this study were several governmentinstitutions in Sleman Regency, namely (1) Sleman Regency Agriculture, Food and FisheriesService, (2) Sleman Regency Land and Spatial Planning Office, (3) Integrated Licensing andInvestment Services Office of Sleman Regency, (4 ) National Land Agency, and (5) RegionalDevelopment Planning Board of Sleman Regency. The results of the study show thatorganizational communication working between several local government institutions forinstitutional strengthening in the case of conversion of agricultural land in Sleman Regency usesorganizational communication with vertical and horizontal direction of communication withwritten and directly formal media with regulative and consultative function.